Ways of using evidence-based medicine in general practice. - Mar, D; Glasziou, P (2001)
General practitioners wanting to practise evidence-based medicine (EBM) are constrained by time factors and the great diversity of clinical problems they deal with. They need experience in knowing what questions to ask, in locating and evaluating the evidence, and in applying it. Conventional searching for the best evidence can be achieved in daily general practice. Sometimes the search can be performed during the consultation, but more often it can be done later and the patient can return for the "result". Case-based journal clubs provide a supportive environment for GPs to work together to find the best evidence at regular meetings. An evidence-based literature search service is being piloted to enhance decision-making for individual patients. A central facility provides the search and interprets the evidence in relation to individual cases. A request form and a "results" format make the service akin to pathology testing or imaging. Using EBM in general practice appears feasible. Major difficulties still exist before it can be practised by all GPs, but it has the potential to change the way doctors update their knowledge.